Effectiveness comparison of ozonated water and povidone iodine 1% on the growth of streptococcus mutans bacterium (in vitro) - Ahyar Riza; Indra Basar; Jessica Sonya (Journal of Dentomaxillofacial Science, 2021)
Objective: The aim of this study is to determine the effectiveness comparison of ozonated water and povidone iodine 1% on the growth of Streptococcus mutans bacterium (in vitro). Material and Methods: In the act of extracting teeth, complications due to tooth extraction may occur due to various factors and also vary in terms. Infection is one of the complications that can occur after tooth extraction. Streptococcus mutans is a member of the normal flora of the oral cavity, but can become pathogenic if the balance of normal flora disturbed. One alternative way of prophylaxis is to use an antiseptic mouthwash. One commonly used antiseptic is povidone iodine 1%. The use of povidone iodine 1% gargle after tooth extraction, incision and drainage is an effective additional treatment in odontogenic infection. Ozone is one of the most powerful antimicrobial agent available for use in dentistry. Mechanism of ozonated water will only affects the bacteria and does not harm the body's cells because the ozone has anti oxidation. Results: The study were analyzed using the Independent T Test and Shapiro-Wilk test. The result are 0.0001. This value was then compared with 0.05 (p <0.05). This show that there is significant differences in the inhibitory diameter between the ozonated water group and povidone iodine 1% group. Conclusion: This study was an experimental study using 2 sample groups, consisting of 16 samples per group.